Efficiency assessment of measures to increase sustainability of the transport system - Makarova, Irina; Shubenkova, Ksenia; Pashkevich, Anton (Transport, 2021)
This paper considers managerial approaches to increase efficiency of the urban transport system such as promotion and integration of sustainable modes of transport, development of public transport route network, renewing the existing vehicle fleet and shift to environmental friendly fuel types in the public transport system. To assess such kind of efficiency, it is proposed to take into account the economic viability of suggested solutions as well as their influence on social sphere, environmental friendliness and sustainability of the urban transport system. The city of Naberezhnye Chelny (Russia) was chosen for the case study, where the following measures were modelled: changes of bus route network and choice of an optimal fleet on routes depending on passenger flow by hours of day. In addition, the efficiency of these measures were assessed. To evaluate the sustainability of the proposed route network, the method of “radar map” was used, which shows both strengths and weaknesses of selected indicators. Together with this evaluation, analysis of risks in managing the urban bus transportation was carried out.